(untitled) - Austin, Michael (New York, 2010)
The Second Edition offers more contemporary readings and provides more help to make the texts accessible for undergraduate readers. Brief overviews of each reading give students a sense of what the piece is about, and detailed headnotes call attention to the rhetoric of each reading to help students focus not only on what the authors say but also on how they say it.
Keywords: English language,Tiếng Anh; Rhetoric,Tu từ học